The rise of a middle class in East and Southern Africa: Implications for food system transformation - David Tschirley; Thomas Reardon; Michael Dolislager; Jason Snyder (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
We examine the implications of the rise of a middle class in East and Southern Africa for food consumption patterns and the food system. A unique classification of food items shows that highly processed food has one-third of the purchased food market, with comparable shares in rural and urban areas (31 per cent vs 35 per cent), and among the vulnerable and upper middle classes (33 per cent vs 41 per cent). By linking FAOSTAT import data to consumption bundles, we show that the net import share falls with income in urban areas. Implications for food system change to 2040 are discussed.
Keywords: D4; O12; O14; O18; Q13; Q18; 330; Africa; food imports; middle class; processed food; urbanization